The Role of Zakat in Supporting SDG 3 and SDG 6 in Madrasahs: A Case Study of BAZNAS Indonesia - Hadid, Marwan; Martina, Martina (UIN Sunan Kudus, 2026)
This study looks at how equity perception and student participation in Indonesian madrasahs are affected by the sanitation renovation program funded by BAZNAS. Path analysis was employed to examine the relationships between female participation, perceived equity of facility access, motivation, and facility quality using quantitative survey data collected from school principals, teachers, and administrative staff across 113 schools in 24 provinces. The results show that students' perceptions of equitable access are greatly enhanced by better facility quality and learning motivation, which in turn significantly raises female participation in school activities. In contrast the reduction of sanitation related illnesses did not show a significant direct association with perceived equity of facility access in the path analysis, indicating that improvements in health conditions aline may not immediately translate into perceptions of fairness in facility use. The findings show that zakat-based infrastructure interventions promote social inclusion, gender equality, and educational well-being by producing both physical and psychological benefits. This study encourages the incorporation of Islamic social finance into frameworks for sustainable education and highlights the developmental potential of productive zakat as a tool of social justice.